Grapevine nursery propagation material as source of fungal trunk disease pathogens in Uruguay - Carbone, María Julia; Gelabert, Matías; Moreira, Victoria; Mondino, Pedro; Alaniz, Sandra (Frontiers in Fungal Biology, 2022)
Grapevine fungal trunk diseases (GTDs) have become a serious problem for grapevines worldwide. Nursery vines infected during the propagation process are considered one of the main ways of dissemination of GTD pathogens. In this study, we examined the status of GTDs in grapevine planting material, from rootstocks and scion mother cuttings to grafted rooted vines ready to plant, according to the local nursery propagation process. During 2018-2019, internal symptoms of GTDs were examined in 2400 propagation materials and fungal isolations were carried out from a subsample of 1026 selected materials. Our results revealed that nursery grapevine plants produced in Uruguay have a high incidence of GTDs, regardless of the scion/rootstock combination. Typical brown to black streaks and sectorial wood necrosis were observed in materials on all propagation stages, with a markedly increasing incidence throughout the nursery process, reaching almost 100% in grafted rooted vines ready to plant. Botryosphaeria dieback, Petri disease and black-foot disease were the main GTDs found. The results showed that Botryosphaeria dieback and Petri disease pathogens infect materials from the early stages of the process, with a marked increase towards the end of the plant production process, whereas black-foot disease pathogens were found exclusively in vines ready to plant. Diaporthe dieback pathogens were also detected in materials in all stages but in a low proportion (less than 10% of infected material). Based on single locus analysis, the 180 isolates selected were placed into eight genera and 89% identified within 22 fungal species associated with GTDs, with Phaeoacremonium oleae and Diaporthe terebinthifolii as new records on grapevine worldwide. Our results have concluded that locally produced vines are one of the main ways of dissemination of GTD pathogens and showed that a nursery sanitation programme is required to reduce the incidence of these diseases.